Screening alternative chemical routes based on inherent chemical process properties data: Methyl methacrylate case study - Mimi Haryani, Hassim; Mohamad Wijayanuddin, Ali, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/